Protecting Human Rights Defenders in Latin America A Legal and Socio-Political Analysis of Brazil - Terto Neto, Ulisses (Governance, Development, and Social Inclusion in Latin America, 2018)
This book offers a legal and socio-political analysis of the Brazilian Program for the Protection of Human Rights Defenders. Discussing Colombian, Guatemalan and Mexican experiences, it fills a gap in the literature regarding Latin American public policy by investigating the creation, work, beneficiaries, broader effects, challenges, and effective ways to improve the Brazilian Program.